2019
DOI: 10.3389/fneur.2018.01176
|View full text |Cite
|
Sign up to set email alerts
|

Vascular, Cognitive, and Psychomental Survey on Elderly Recycling Volunteers in Northern Taiwan

Abstract: Background: Stroke and dementia represent frequent causes of psychophysical and socioeconomic burdens. We conducted a vascular, cognitive, and psychomental survey involving elderly volunteers at community-based recycling stations in Northern Taiwan.Methods: Recycling volunteers aged ≥60 years were surveyed. We recorded seven parameters, namely (1) body mass index (BMI), (2) fasting glucose, (3) fasting cholesterol, (4) ankle-brachial index (ABI), (5) carotid duplex sonography, (6) five-item Brief Symptom Ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
(57 reference statements)
1
9
0
Order By: Relevance
“…As shown in Table 1, there was a high AD8-positive rate (28.2%, suspected dementia) in our study, compatible with the previous reports of using AD8 in the hospital 22,23 but much higher than the AD8 screening results in the non-hospital settings 24,25 . There are some possible explanations for the high positive rate of AD8 in our study.…”
Section: Discussionsupporting
confidence: 92%
“…As shown in Table 1, there was a high AD8-positive rate (28.2%, suspected dementia) in our study, compatible with the previous reports of using AD8 in the hospital 22,23 but much higher than the AD8 screening results in the non-hospital settings 24,25 . There are some possible explanations for the high positive rate of AD8 in our study.…”
Section: Discussionsupporting
confidence: 92%
“…34 In addition, HSCT patients who have community-acquired pulmonary viral infections can have severe lower respiratory tract involvement, late airway outflow obstruction, and multiple fungal and bacterial coinfections. 36 Postsurgical infection is a common but often severe complication in cancer patients. Depending on the type, location, tumor size, lymph node involvement, and organ involvement, subsequent infectious complications can range from minor to moderate or severe.…”
Section: Immunotherapymentioning
confidence: 99%
“…Despite the small sample size in this study, the IMT and QIMT exhibited positive linear correlations with age. Previous studies have shown that men and older people have higher IMT than their female and younger counterparts [ 22 ]. In this study, the mean IMT did not differ between men and women because women were older than men, which may have counterweighted the effect of sex.…”
Section: Discussionmentioning
confidence: 99%